Implementation of DESMOS as a Teaching Tool in Graphing Functions in the New Normal - Dy, Audric Curtis (SAFE-Network, 2024)
Before the implementation of online learning, students graphed functions on paper using either a ballpen or pencil. However, online learning materials including online graphing calculators were being encouraged to be used since the modality had shifted into online learning. DESMOS is one of the online learning materials that can be used in graphing functions. This study aimed to evaluate the effectiveness of the implementation of DESMOS as a graphing tool for teachers and students together with the benefits of this software together with the perceptions towards it. The study was conducted with 23 Grade 11 students taking up Accountancy and Business Management during the classes of Statistics and Probability. The research design used was mixed consisting of comparative statistical techniques and narrative analysis. The interventions involving DESMOS were done virtually through Google Meet. Their skills before and after the interventions involving DESMOS were compared and based on the statistical aspect, there was a significant difference between the skills before and after the interventions with a t-statistical value of -3.78, which was lower than the critical value of -2.074. Besides, the students were able to collaborate in terms of tasks and reflect on what they had learned in DESMOS, and they were able to see DESMOS as an accessible, convenient, and effective graphing tool. DESMOS should be widely used as a teaching tool in graphing functions so students will be able to appreciate technology with mathematics since people are now living in the era of technology.